LIGHT SCATTERING FROM MICROMETRIC MINERAL DUST AND AGGREGATE PARTICLES: EFFECTS OF SHAPE AND STRUCTURE APPLIED TO PALEOCLIMATE STUDIES. - CREMONESI PLAJA, LLORENC (Università degli Studi di Milano, 2019)
Atmospheric aerosol is known to impact the Earth radiative energy balance and the local temperature in the atmosphere by interacting with both solar and terrestrial radiation. The extent of this direct and indirect contribution has not to date been determined with adequate accuracy. The present work examines the scattering of visible light from non-spherical particles in the micrometric size range, such as mineral dust and colloidal aggregates, with a focus on the effect of their shape and morphology. Lorenz–Mie scattering and effective medium approximations are currently the main theoretical approaches to model the optical properties of aerosol particles, although their effectiveness has been recently called into question. This thesis provides an overview of the experimental results from Antarctic and Alpine ice cores by applying optical techniques with a particle-by-particle approach. A particular attention is also given to the study of colloidal aggregates as a model for complex particles. Specifically, we rely on Single Particle Extinction and Scattering and Near Field Scattering on flowing samples, which give model-independent results. On the theoretical side, an interpretation of scattering data is given in terms of the structure factor of the particles, beyond the spherical approximation. The experimental findings are also supported by extensive simulations based on the Discrete Dipole Approximation. By measuring two optical parameters simultaneously, it is possible to distinguish compact particles from aggregates of smaller particles occurring in deep ice cores. More generally, while some scattering parameters are correctly predicted by well-established models such as the Rayleigh–Debye–Gans theory, it is found that particle shape and internal structure have a significant effect on their complex scattering amplitude. Similarly, the discrepancy between the results obtained from two different approaches for particle sizing can be ascribed to particle shape. Moreover, there is evidence that effective medium ...